A survey of the quality of life of Filipino women in the perimenopausal period using a validated women's health questionnaire, Filipino-version - Sun-Cua, Alice M.
Participants: Two hundred seventy nine Filipino women, 43-48 years old, were included in the study. Objectives: The General Objective was to examine the quality of life of Filipino perimenopausal women aged 43 to 48 years using a validated Women's Health Questionnaire, a health Quality of Life instrument for perimenopausal women. Specific Objectives were (1) to culturally validate the Women's Health Questionnaire in its different domains, and (2) to describe the impact of menopausal symptoms on the quality of life in Filipino women using this instrument after the validating process. Setting: San Juan De Dios Hospital, Pasay City Design: Cross-sectional Instrumentation: Women's Health Questionnaire in English and Filipino. Data Collection methods: Opportunistic recruitment of women consulting the OPD clinics of pay and service departments, companions of these women, watchers of in-patients hospital staff, college staff. Data Analysis: Using STATA 7, imputation was done for missing data. Factor analysis and varimax rotation were done to determine under which domains the answers loaded. Results: Content and construct validity were confirmed. Reliability was established with a high Cronbach alpha for internal consistency or homogeneity. Three domains emerged: Physical/Somatoic, Vasomotor, and Emotional/Anxiety. A separate analysis of the global sense of well-being of the women showed that quality of life was high, in spite of the presence, vasomotor, and emotional symptoms. Conclusions: The translated Filipino version of the Women's Health Questionnaire is a valid and reliable tool to assess the health-Quality of life of Filipino women 43-48 years old. Half of them experience physical, vasomotor, and emotional symptoms secondary to the hormonal fluctuations expected in their age group, but overall they were satisfied with the quality of their lives, based on the very high scores particularly in the questions pertaining to Global Sense of Well-Being. Filipino perimenopausal women are not overly concerned with the menopausal transition, and view the change in a positive light.